Estimating optimal operationtime of Korral Kools on dairycows in a desert environment - X.A. Ortiz; John F. Smith; Barry J. Bradford; Joseph P. Harner (Kansas Agricultural Experiment Station Research Reports, 2008)
Developing management strategies for Korral Kools will help producers provide cooling in the housing area while minimizing the operational cost of the Korral Kools system. Two experiments were conducted at a dairy in Saudi Arabia to evaluate operational time of Korral Kools for multiparous and primiparous dairy cows. For multiparous cows, running time per day of Korral Kools should be continuous, but for primiparous cows, no difference in performance was detected between 21 and 24 hours. However, producers need to be careful when reducing daily operation time of Korral Kools for primiparous cows because elevated core body temperatures were observed in both treatments.; Dairy Day, 2008, Kansas State University, Manhattan, KS, 2008; Dairy Research, 2008 is known as Dairy Day, 2008
Keywords: Dairy Day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-134-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1002; Dairy; Operation time; Korral Kools; Desert enviroment